Pendampingan Pembuatan E-LKPD Bermuatan Literasi Numerasi Untuk Meningkatkan Kompetensi Digital Calon Guru Sekolah Dasar Di FKIP UNISSULA - Rida Fironika Kusumadewi; Nuhyal Ulia; Setyo Wuri Kartika Nugraheni; Trijoko Bagus Setyawan (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
Strengthening numeracy literacy and digital competence is an essential requirement in preparing prospective elementary school teachers who are able to meet the challenges of 21st-century learning. However, the needs analysis revealed that students of the Elementary School Teacher Education Program (PGSD) still experience difficulties in developing digital teaching materials that integrate numeracy literacy in a contextual manner. This community service activity aims to improve the competence of PGSD students in designing and developing E-LKPD based on numeracy literacy. The method used is Asset-Based Community Development (ABCD), which includes needs analysis, training, workshops, mentoring, and product evaluation stages. The activity involved 30 PGSD students participating in the mentoring program for developing technology-based E-LKPD. The results showed an increase in participants’ understanding of numeracy literacy from 52.3% to 87.6%. While 93% of participants successfully produced E-LKPD categorized as good to very good. The developed products include contextual numeracy activities, interactive features, and are applicable in elementary school learning, contributing to the readiness of prospective teachers to develop innovative and contextual digital learning.